Detailed investigations of ZnO photoelectrodes preparation for dye sensitized solar cells - Marczak, Renata; Werner, Fabian; Ahmad, Rameez; Lobaz, Volodymyr; Guldi, Dirk Michael; Peukert, Wolfgang (Langmuir, 2011)
Wurtzite ZnO hexagonal nanopyramids were successfully synthesized in the liquid phase from homogeneous methanolic solutions of zinc acetate and tetramethylammonium hydroxide at an excess of zinc ions. The formation and properties of the nanocrystals were examined as a function of synthesis conditions. No significant influence of the [Zn ]/[OH ] ratio was noticed on the final particle size, in spite of increased amounts of OH ions, which tend to accelerate the particle nucleation and growth. Nevertheless, the reactant concentration ratio influences the surface properties of the ZnO nanocrystals. Mesoporous ZnO films were prepared by doctor blading ethanolic pastes containing ZnO nanoparticles and ethyl cellulose onto FTO conductive glass substrate followed by calcination. Additionally, the influence of a plasticizer (triacetin)-used during the paste preparation-on the film quality was investigated. A higher content of ZnO nanoparticles and plasticizer in the pastes improved the film quality. Four different temperatures (i.e., 400, 425, 450, and 475 °C) were used for the film calcination and their influence on the structural properties of the films was characterized. In principle, increasing the calcination temperature goes hand in hand with an increase of particle size, as well as the pore diameter and reduction of the surface area. Suitable mesoporous films were employed as photoanodes in dye sensitized solar cells (DSSCs). In order to assess the effect of the varied parameters on complete DSSC devices-using cis-diisothiocyanato-bis(2,2′- bipyridyl-4,4′-dicarboxylato) ruthenium(II)bis(tetrabutylammonium (N719) as a sensitizer-incident photon to current efficiency (IPCE) and current voltage measurements were carried out. The IPCE measurements confirmed photoinduced electron injection from the dye, reaching IPCE values up to 76%. Furthermore, current-voltage characteristics of complete cells emphasized the importance of the proper preparation methods and temperatures. These features are important assets for the preparation of nanocrystalline ZnO based photoelectrodes and for improving the DSSC performance. © 2011 American Chemical Society.

Highly magnetizable superparamagnetic colloidal aggregates with narrowed size distribution from ferrofluid emulsion - Lobaz, Volodymyr; Klupp Taylor, Robin; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2012)
The formation of spherical superparamagnetic colloidal aggregates of magnetite nanoparticles by emulsification of a ferrofluid and subsequent solvent evaporation has been systematically studied. The colloidal aggregates occur as a dense sphere with magnetite nanoparticles randomly packed and preserved particle-particle separation due to chemisorbed oleic acid. The voids between nanoparticles are filled with solvent and free oleic acid. The latter was found to influence the formation of colloidal aggregates and their surface properties. The choice of surfactant, whether low molecular weight or polymeric, was shown to lead to the colloidal aggregates having tailored interfacial behavior. Magnetization measurements at ambient temperature revealed that the magnetite colloidal aggregates preserve the superparamagnetic properties of the starting nanoparticle units and show high saturation magnetization values up to 57. emu/g. The size distribution of magnetite nanoparticle colloidal aggregates produced by such an approach was found to be a function of emulsion droplet breakup - coalescence and stabilization kinetics and therefore is influenced by the emulsification process conditions and concentrations of the emulsion compounds. © 2012 Elsevier In
Keywords: Colloidal aggregate; Emulsion; Magnetite nanoparticle; Superparamagnetic particle

Layer-by-Layer Assemblies of Catechol-Functionalized TiO2 Nanoparticles and Porphyrins through Electrostatic Interactions - Burger, Alexandra; Costa, Ruben Dario; Lobaz, Volodymyr; Peukert, Wolfgang; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
In the current work, we present the successful functionalization and stabilization of P-25 TiO2 nanoparticles by means of N1,N7-bis(3-(4-tert-butyl-pyridium-methyl)phenyl)-4-(3-(3-(4-tert-butyl-pyridinium-methyl)phenylamino)-3-oxopropyl)-4-(3,4-dihydroxybenzamido)heptanediamide tribromide (1). The design of the latter is aimed at nanoparticle functionalization and stabilization with organic building blocks. On one hand, 1 features a catechol anchor to enable its covalent grafting onto the TiO2 surface, and on the other hand, positively charged pyridine groups at its periphery to prevent TiO2 agglomeration through electrostatic repulsion. The success of functionalization and stabilization was corroborated by thermogravimetric analysis, dynamic light-scattering, and zeta potential measurements. As a complement to this, the formation of layer-by-layer assemblies, which are governed by electrostatic interactions, by alternate deposition of functionalized TiO2 nanoparticles and two negatively charged porphyrin derivatives, that is, 5,10,15,20-(phenoxyacetic acid)-porphyrin (2) and 5,10,15,20-(4-(2-ethoxycarbonyl)-4-(2-phenoxyacetamido)heptanedioic acid)-porphyrin (3), is documented. To this end, the layer-by-layer deposition is monitored by UV/Vis spectroscopy, scanning electron microscopy, ellipsometry, and profilometry techniques. The resulting assemblies are utilized for the construction and testing of novel solar cells. From stable and repeatable photocurrents generated during several ön-offc̈ycles of illumination, we derive monochromatic incident photo-to-current conversion efficiencies of around 3 \

Self-alignment of zinc oxide nanorods into a 3D-smectic phase - Schäfer, Stefan; Srikantharajah, Rubitha; Klaumünzer, Martin; Lobaz, Volodymyr; Voigt, Michael; Peukert, Wolfgang (Thin Solid Films, 2014)
We focus on thin films from ZnO nanorod dispersions in order to generate a high lateral order and a dense space filling structure applicable e. g. in printed optoelectronic devices. Highly stable dispersions with a solid content of up to 60 wt.% in ethanol were prepared using trioxadecanoic acid as stabilizer. With the dispersions we prepared thin films on substrates with a 3D-smectic phase in lateral dimension of cm2 and thicknesses from below 100 nm up to 1 μm. We show how the concentration of the initial solid content is influencing the formation of domains in our films and discuss the self-assembly process into ordered structures.